2020
DOI: 10.20956/ijab.v4i1.9168
|View full text |Cite
|
Sign up to set email alerts
|

Reevaluation of Land Fitness For Soybean Plant in Kabamatan Stabat, Langkat District

Abstract: A decrease in the area of soybean farming has an effect on reducing soybean production from year to year so that it has not been able to meet the needs of national soybean consumption. Land suitability assessment is an effort to be able to optimize land use. In the process of assessing land suitability manually, it is considered inaccurate. The purpose of this study was to determine the land suitability class for soybean plants. The land suitability classification system used is the FAO land suitability classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…The increase in the number of chromosomes using colchicine-induced polyploidisation was reported to result in plants showing enhanced sizes of morphological characters, such as larger leaves, flowers, and seeds (Table 1). Eng and Ho [3] also reported that this artificial polyploidisation can be used as a strategy for the adaptation of species, particularly of horticultural crops. In legumes, evaluation of nodule number, nodule size, terminal bacteroid differentiation, and symbionts quality (nodule environment, partner choice, host sanctions, etc.)…”
Section: Impact Of Polyploidisation On Alleviating the Effects Of Dro...mentioning
confidence: 98%
See 2 more Smart Citations
“…The increase in the number of chromosomes using colchicine-induced polyploidisation was reported to result in plants showing enhanced sizes of morphological characters, such as larger leaves, flowers, and seeds (Table 1). Eng and Ho [3] also reported that this artificial polyploidisation can be used as a strategy for the adaptation of species, particularly of horticultural crops. In legumes, evaluation of nodule number, nodule size, terminal bacteroid differentiation, and symbionts quality (nodule environment, partner choice, host sanctions, etc.)…”
Section: Impact Of Polyploidisation On Alleviating the Effects Of Dro...mentioning
confidence: 98%
“…Even though the routine use of artificial doubling of chromosome complements in legumes remains highly improbable, especially due to the recalcitrance in crops such as soybean, cowpea and faba bean, the effect of induced polyploidy in leguminous crops, as compared to other non-leguminous crop species, and the possible differential response of polyploidised varieties to environmental constraints will still present major challenges. This group of dicot crops overwhelmingly appear to fail in responding better to genetic improvement protocols, especially under the changing climatic conditions, because of the lack of routine and effective breeding systems [1][2][3][4][5]50,68]. While genetic engineering and induced polyploidisation continue to seem unachievable, stable and efficiently reproducible protocols for the development of legume polyploids remain a prerequisite to deal with the adverse effects of drought stress.…”
Section: Ploidy Stability Under Drought Stress Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, this rapid population upsurge, malnutrition, poverty, unemployment, and climate change driven biotic as well as abiotic stress factors dramatically raises pressure on the food systems, especially agricultural legume production [2]. Nevertheless, the inclusion of improved leguminous crop varieties in cropping systems plays a significant role in alleviating the abovementioned challenges, particularly, global issues such as food insecurity, decreasing soil fertility, and developing climate resilient cultivars that can be grown under adverse environmental conditions [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Land suitability evaluation is a process of assessing land resources potential based on pre-existing land suitability [9]. The most basic land suitability evaluation technique that is often used matches land suitability with land and weather characteristics which then produces limiting factors [10] [11]. The development of artificial intelligence can also be used, such as applying a machine learning method for data classification [12], which in this study is the suitability of soybean land.…”
Section: Introductionmentioning
confidence: 99%